Fifth Grade Students' Critical Thinking Skills in the Post-Pandemic Face-to-Face Learning Period - I Komang Wahyu Aditya Putra; Putu Nanci Riastini; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2022)
Students have low critical thinking skills due to the lack of teachers designing learning activities that can improve necessary thinking skills during the pandemic. This study aims to analyze the essential thinking skills of fifth-grade students during the post-pandemic face-to-face learning period. This type of research is descriptive research. This research is a descriptive survey. The research population amounted to 296 students. Sampling using cluster random sampling. The sample of School Research in the City amounted to 105. The sample of Research Schools in the Village amounted to 64. The data collection method used was the test method. The instrument used in data collection is a description test question. The technique used to analyze the data is descriptive statistical analysis. The study’s average results of the critical thinking skills of fifth-grade elementary school students during the face-to-face post-pandemic period were in the high category. The average score for essential thinking skills of city cluster students is 67.18, and the average score for village cluster students' necessary thinking skills is 70.